Effects of body mass index and insulin resistance on first-time assisted conception and perinatal outcomes in young polycystic ovary syndrome patients - Guo, Jiayu; Chen, Yuanhui; Jiang, Yilin; Zhang, Cuilian (Frontiers in Endocrinology, 2023)
Objective The objective of the study was to explore the effect of body mass index (BMI) and insulin resistance (IR) levels on first-time assisted conception results and perinatal outcomes in young polycystic ovary syndrome (PCOS) patients. Design This was a single-center, retrospective, observational cohort study. Patients Young women with PCOS undergoing their first embryo transfer were included in the study. Main outcome measure Early pregnancy loss rate was the main outcome measure. Results The early pregnancy loss rate in the overweight + insulin resistance group (OW+IR group) was significantly higher than that in the non-overweight + non-insulin resistance group (NOW+NIR group) (18.16% vs. 9.02%, Bonferroni correction, P = 0.012). The early pregnancy loss rate in the non-overweight + insulin resistance group (NOW+IR group) and overweight + non-insulin resistance group (OW+NIR group) (18.18% and 17.14%, respectively) were also higher than that in the NOW+NIR group (6.07%), but the difference was not statistically significant (Bonferroni correction, all P > 0.05). No significant difference was found in clinical pregnancy rate, live birth rate, and macrosomia rate (all P > 0.05). After adjusting for confounding factors, BMI and IR levels were identified as independent risk factors for early pregnancy loss rate. Conclusion BMI and IR levels are independent risk factors for early pregnancy loss in young PCOS patients during the first embryo transfer cycle. Multiple indicators should be considered when assessing pregnancy outcomes, which will promote individualized pregnancy guidance and treatment procedures for PCOS patients.